Pengaruh Perilaku Pemimpin, Job Characteristics dan Job Demands Terhadap Perilaku Kerja Inovatif Karyawan PT Adaro Indonesia - Mekka Riadhah; Saladin Ghalib; R. R Yulianti Prihatiningrum (Universitas Lambung Mangkurat, 2022)
This research is aimed to analyse effect of leader behavior, job characteristics and job demands on employees’ innovative work behavior. The three independent variable are analyzed according to 4 phases of the dependent variable (opportunity exploration, idea generation, idea championing and idea application). Deeper analysis is also conducted on each function (core, technical and support). Research data is collected from 116 supervisors who work at PT Adaro Indonesia and classified into 3 functions (core, technical and support). The questionnaire is distributed and answered online. The data is analyzed by utilizing regression method on Minitab 19.The result shows 8.93% employees’ innovative work behavior is affected by leader behavior, job characteristics and job demand. Job characteristics is proven to be affecting but leader behavior and job demands are non-affecting. Four-phase analysis reveals job characteristics and leader behavior have effect, each on idea generation and idea application consecutively. Function-based analysis presents two facts: leader behavior has effect on idea championing and idea application at core function and job characteristics has effect on idea generation and idea application at support function. Keywords: innovative work behavior, leader behavior, job characteristics, job demands